eu, autora – corpo e escrita em fractal: Elena Ferrante, frantumaglia e smarginatura - Dantas, Tatianne Santos (2023)
This thesis is meant to offer a survey through the corpus of Elena Ferrante, giving detailed attention to the non-fiction books La frantumaglia (2016), L‟invenzione occasionale (2019) and I margini e il dettato (2021), mapping the landscape that body and writing create through the words frantumaglia and smarginatura. La frantumaglia is the title of a collection of papers, tesserae and letters, in which Elena Ferrante begins the process of constructing a body of her own by means of her narrators. A heritage from her family‘s lexicon, Frantumaglia is a word coming from the Neapolitan dialect but with a close connection with frantumare, an Italian verb that describes the act of breaking something down to pieces. Besides, frantumare has the same etymological root as ‗fractal‘, from the latim 'fractus', meaning fraction as well as broken. That is, through frantumaglia one seems to be inevitably conducted towards an image in pieces, with each fragment harboring the whole of the image of which is but a part, resembling a fractal. Smarginatura, by its turn, delivers a mirroring of Ferrante‘s maternal lexicon, once the word emerges as a creation by one of the characters present in the fictional works. The word is created to describe the feeling of loosing the margins of one‘s body and the consequent dissolution of the ‗I‘ among people and objects in the nearby surroundings. In I margini e il dettato (2021), the author establishes a straight connection between smarginatura and writing, and it is through intertwining frantumaglia, smarginatura and the poetic tone of Ferrante‘s books that I put forth how she structures a body which presents itself by means of writing, reenacting a fractal in its development. In this attempt, I rely on the company of writers who already explore the topics in Elena Ferrante explored in this thesis, being of unparalleled presence the work of Maria Gabriela Llansol. Concerning the theoretical basis, I invoque Eliane Robert de Moraes (2017) and her addressing of body fragmentation in the arts of the twentieth century, as well as the notion of body and exscribed offered by JeanLuc Nancy (2000, 2015). To better comprehend the notion of fractal through the lens of the mise en abyme, I consider works on the topic by Lucien Dallenbach (1977), Véronique Labeille (2011), Alain Goulet (2006), Mariângela Alonso (2017), among others, and, in Psychoanalysis, I debate an elaboration made by Jacques Lacan (1998) and Luce Irigaray (2017) concerning mirror, the behold of the Other and the relation with writing. The theoretical basis for mise en abyme and Psychoanalysis is the support I rely on in order to properly consider how thought structures the image of one‘s body from the mirror, allowing me also to explore the possibility of going beyond this framework through the notions issuing from the discussions surrounding frantumaglia, smarginatura and fractal shapes. To render possible this movement, I also consider the dialogue Elena Ferrante establishes with the feminist critic, specially the ones entertained with Adrienne Rich (2017) and Eurídice Figueiredo (2013).__________________________________________________________________________________________________________________